Auréola de metamorfismo de contato da porção oeste do granito Meruoca - Nordeste do Ceará - CORDEIRO, Elias Antônio Cabral (2019)
The contact metamorphism represents the best example of thermal transfer emanated by granitic plutons at shallow crustal levels, with mineral and textural changes in rocks, resulting in an extremely compact and solid rock, called a hornfels. In the northwestern region of Ceará State, in the Médio Coreaú Domain, northwestern sector of the Borborema Province, this type of metamorphism has been reported around the granitic batholiths, which arise mainly near shear zones, such as Granite Meruoca. This work aims to characterize the contact metamorphism that occurs in host rocks of the western portion of the Granite Meruoca, represented by the sandstones of the Pacujá Formation (Jaibaras Group) through petrographic analysis. The studied profile is located between the cities of Alcântara and Coreaú (CE), following the road CE-241 toward the Meruoca Mountains. We studied 5 outcrops (2008-TEC-01 to 05), with collect 14 samples, which were made 15 thin sections. The petrographic study revealed detrital sedimentary rocks, ranging from sandstone to conglomeratic sandstones and compositionally, impure arkose to lithic arkose, containing portions of pelitic, carbonate and basic composition. The first metamorphic stage (M0) is represented by the rocks outside from the aureole, which show changes generated by burial and hydrothermal metamorphism in conditions of low greenschist facies, chlorite zone (T=300-350°C; P=2-3 kbar). The aureole starts at approximately 500 m from the Meruoca Granite (stage M1), with crystallization of biotite, which does not occur in stage M0, creating a dark and very compact rock in conditions of facies albite-epidote-hornfels, the biotite isograd (350-400°C). On contact with granite, can be viewed at full transformations, displaying rocks totally recrystallized, with structure nodulose or maculose, typical of hornfels. The paragenesis is composed of microcline + quartz + plagioclase + clinopyroxene (diopside) + hornblende in conditions of hornblende hornfels facies, garnet isograd (T = 600°C; P=2 kbar) in the third metamorphic stage (M3). This rock was classified as diopside-hornblende-microcline hornfels.